Design and Characterization of New Dinuclear Macrocyclic Dithiocarbamate Complexes by the Preparation of a Free Ligand Derived from Isopropylamine - Al-Mohammadi, Noor Al-Huda A.H; Al-Fahdawi, Aeed S.M; Al-Janabi, Sattar S.I (Iraqi Journal of Science, 2021)
The synthesis and structural characterization of new dithiocarbamate (DTC) ligand and some of its dinuclear transition metal complexes are described. The free dithiocarbamate ligand was prepared through several synthetic routes, including Schiff-base formation. The reaction of 2-aminopropane with terephthaldehyde leads to the formation of Schiff_base which is reduced by methanolic NaBH4 to the corresponding secondary diamine. Diamine( N,N’_ (1,4 phenylenebis (methylene)) bis(propan-2 amine)) reacts with (CS2) in a basic solution of (KOH) to provide the corresponding bis(dithiocarbamate) free_ligand, which undergoes complexation with the appropriate metal (II) chloride to constitute macrocyclic complexes. Characterization of the ligand and its complexes was achieved by FTIR, UV-Vis, melting points, conductance, magnetic susceptibility, and 1H, 13C NMR spectroscopy. The analytical and spectroscopic data were employed to obtain the suggested geometries around metal centres. These studies revealed the formation of dinuclear macrocyclic complexes of the general formula [M(L)]2 (where M= Mn(II) , Fe(II), Co(II), Ni(II), Cu(II) and Zn(II)), with tetrahedral. geometries for Mn(II) , Fe(II), Co(II) and Zn(II), and square. planar geometry with Ni(II) and Cu(II) complexes.